Hydrolysis of L-Histidine Methyl Ester - Cole, E. R (Thrombosis and Haemostasis, 1968)
The hydrolysis of L-histidine methyl ester (HME) by bovine thrombin preparations has been investigated. Activation of purified bovine prothrombin in 25% sodium citrate solution resulted in the simultaneous development of fibrinogen clotting activity and of TAME and HME esterase activities. Most of the HME esterase activity was identified with fibrinogen clotting activity on sequential chromatography of activated prothrombin on DEAE-cellulose and Amberlite CG-50 resin columns, although some HME esterase activity could be demonstrated in concentrates of the autoprothrombin C fraction. The optimum pH for HME hydrolysis by thrombin was found at 7.6 in phosphate and Tris buffered reactions. Tris buffer and other amines depress HME esterase activity of thrombin, while sodium cholate accelerates the reaction. The Michaelis constant, Km, was estimated to be 0.134 M at pH 7.6 in phosphate buffer and at 37° C.